Community hospitals and their services in the NHS: identifying transferable learning from international developments - scoping review, systematic review, country reports and case studies - Emma Pitchforth; Ellen Nolte; Jennie Corbett; Céline Miani; Eleanor Winpenny; Edwin van Teijlingen; Natasha Elmore; Sarah King; Sarah Ball; Joanna Miler; Tom Ling (National Institute for Health Research, 2017)
Background: The notion of a community hospital in England is evolving from the traditional model of a local hospital staffed by general practitioners and nurses and serving mainly rural populations. Along with the diversification of models, there is a renewed policy interest in community hospitals and their potential to deliver integrated care. However, there is a need to better understand the role of different models of community hospitals within the wider health economy and an opportunity to learn from experiences of other countries to inform this potential. Objectives: This study sought to (1) define the nature and scope of service provision models that fit under the umbrella term 'community hospital' in the UK and other high-income countries, (2) analyse evidence of their effectiveness and efficiency, (3) explore the wider role and impact of community engagement in community hospitals, (4) understand how models in other countries operate and asses their role within the wider health-care system, and (5) identify the potential for community hospitals to perform an integrative role in the delivery of health and social care. Methods: A multimethod study including a scoping review of community hospital models, a linked systematic review of their effectiveness and efficiency, an analysis of experiences in Australia, Finland, Italy, Norway and Scotland, and case studies of four community hospitals in Finland, Italy and Scotland. Results: The evidence reviews found that community hospitals provide a diverse range of services, spanning primary, secondary and long-term care in geographical and health system contexts. They can offer an effective and efficient alternative to acute hospitals. Patient experience was frequently reported to be better at community hospitals, and the cost-effectiveness of some models was found to be similar to that of general hospitals, although evidence was limited. Evidence from other countries showed that community hospitals provide a wide spectrum of health services that lie on a continuum between serving a 'geographic purpose' and having a specific population focus, mainly older people. Structures continue to evolve as countries embark on major reforms to integrate health and social care. Case studies highlighted that it is important to consider local and national contexts when looking at how to transfer models across settings, how to overcome barriers to integration beyond location and how the community should be best represented. Limitations: The use of a restricted definition may have excluded some relevant community hospital models, and the small number of countries and case studies included for comparison may limit the transferability of findings for England. Although this research provides detailed insights into community hospitals in five countries, it was not in its scope to include the perspective of patients in any depth. Conclusions: At a time when emphasis is being placed on integrated and community-based care, community hospitals have the potential to assume a more strategic role in health-care delivery locally, providing care closer to people's homes. There is a need for more research into the effectiveness and cost-effectiveness of community hospitals, the role of the community and optimal staff profile(s). Funding: The National Institute for Health Research Health Services and Delivery Research programme.